2013
DOI: 10.1111/1755-0998.12207
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of Orchidaceae in Korea

Abstract: Species of Orchidaceae are under severe threat of extinction mainly due to overcollection and habitat destruction; accurate identification of orchid species is critical in conservation biology and sustainable utilization of orchids as plant resources. We examined 647 sequences of the cpDNA regions rbcL, matK, atpF-atpH IGS, psbK-psbI IGS and trnH-psbA IGS from 89 orchid species (95 taxa) and four outgroup taxa to develop an efficient DNA barcode for Orchidaceae in Korea. The five cpDNA barcode regions were suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 40 publications
1
61
0
2
Order By: Relevance
“…Although some methods have been proposed for the Orchidaceae, our work showed that it is possible to discriminate between C. walkeriana and C. loddigesii based only on ITS region, but the inclusion of other high variable markers could be valuable to discriminate all of the other species, as found by Kim et al (2014).Therefore, taking into account the current economic importance and conservation status of both species, such region provides a rapid identification method to differentiate the species C. walkeriana and C. loddigesii, with a great power of discrimination and precise identification of these two orchid species.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Although some methods have been proposed for the Orchidaceae, our work showed that it is possible to discriminate between C. walkeriana and C. loddigesii based only on ITS region, but the inclusion of other high variable markers could be valuable to discriminate all of the other species, as found by Kim et al (2014).Therefore, taking into account the current economic importance and conservation status of both species, such region provides a rapid identification method to differentiate the species C. walkeriana and C. loddigesii, with a great power of discrimination and precise identification of these two orchid species.…”
Section: Resultsmentioning
confidence: 64%
“…These were successfully implemented in barcoding species of the orchid genus Dendrobium. For other genus of Orchidaceae from Korea, Kim et al (2014) used another combination of DNA barcodes, based on four regions combined, and reached a 98.8% species resolution…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trình tự các chuỗi vùng đệm giữa các gen hay trình tự các chuỗi không mã của các gen hoặc giữa hai gen (trnL (UAA), rbcL-atpB cũng được sử dụng [130,208]. Trình tự các vùng gen rbcL, matK, atpF-atpH IGS, psbK-psbI IGS và trnH-psbA IGS còn được dùng cho mã vạch (barcode) ở các loài lan [87].…”
Section: Kỹ Thuật Phân Tích Các Rna Vận Chuyển Lục Lạpunclassified
“…Besides this, the species can be transported in a vegetative state, as seeds or as fragments [3]. Accurate authentication of orchid species is critical for biodiversity conservation and effective utilisation of orchids as plant resources [4].…”
Section: Introductionmentioning
confidence: 99%